Implementation policy for the fiber optic Infrastructure development in Indonesia - Aji, Lessy Sutiyono (SEAN Institute, 2024)
Equal distribution is essential to deploying fiber optics in various sub-districts to achieve internet speeds of up to 100 Mbps by the government's target. However, the distribution of fiber optic infrastructure is not evenly distributed; it is only concentrated in big cities. This policy paper aims to find alternative fiber optic development methods from a legal and institutional perspective. So, it can be a recommendation for the Ministry of Communication and Information, especially for the Director General of Post and Information Technology, to make future policies for developing fiber optic networks where no network is available. The method used is a normative law study of the current legal bases and institutional forms to provide fiber optic infrastructure. The results show that the Central Government and Local Government can assist in implementing telecommunications by providing passive infrastructure, in this case, optical fiber, poles, and towers. In this case, the relevant stakeholders are the Ministry of Communication and Information, Local Government, Telecommunication Operators, and State-Owned Enterprises. Based on the assessment of study alternatives, the policy options that can be selected to implement the sub-district fiber optic development program are assigned to state-owned enterprises to build fiber optic infrastructure in the district where the infrastructure is unavailable.